2012
DOI: 10.1093/intqhc/mzs013
|View full text |Cite
|
Sign up to set email alerts
|

Using client experiences for quality improvement in long-term care organizations

Abstract: Although measuring client experiences obligatory, it is not sufficient guarantee that client feedback is used for quality improvement. Although measuring client experiences has led to various improvement initiatives, their effectiveness remains unclear. There is need for guidance on effective improvement of client experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Healthcare providers and professionals themselves are also responsible for the quality of care. Their aim is more internally driven, namely to improve the quality of care and to make visible their contribution to patient outcomes [39,40]. However, our research showed that nurses do not receive feedback on their scores and they are not aware that they could – and even should – use these data to monitor and improve the quality of their work.…”
Section: Discussionmentioning
confidence: 92%
“…Healthcare providers and professionals themselves are also responsible for the quality of care. Their aim is more internally driven, namely to improve the quality of care and to make visible their contribution to patient outcomes [39,40]. However, our research showed that nurses do not receive feedback on their scores and they are not aware that they could – and even should – use these data to monitor and improve the quality of their work.…”
Section: Discussionmentioning
confidence: 92%
“…Studies in the USA have shown that homes reorganized quality improvement programs and started new quality-assurance programs in response to public performance scores [10,12,29]. Although there are no Dutch reports on specific actions taken by nursing homes, residential care facilities or homecare organizations to improve their scores, one qualitative study indicated that organizations start various quality improvement activities in response to the CQI results [30]. …”
Section: Discussionmentioning
confidence: 99%
“…If insurers indicate that a certain quality aspect is important and reward higher scores, organizations will probably improve more on those quality aspects. For the care plan , health insurers also have their own teams that perform administrative controls and trigger improvement in this area [30]. The change scores of some indicators of the mail questionnaires for representatives and assisted-living clients are close to zero or even slightly negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this composition - only one in four members is a client - needs attention [14]. When entering a home, clients are elderly and have physical complaints that limit them in joining the client council.…”
Section: Discussionmentioning
confidence: 99%